impacto de las noticias falsas sobre política nacional en la percepción de los estudiantes de los primeros semestres de la facultad de cc. ss de la utmach - Medina Paladines, Camila Estefania; Solis Cedeño Tony Jared (Machala, 2025)
Fake news or fake news represents a significant problem in today's society, especially in the political sphere, where its dissemination can influence the perception and decision-making of citizens. This research analyzes the impact of fake news about national politics on the perception of students in the first semesters of the Faculty of Social Sciences of the Technical University of Machala. The study used a mixed approach, combining surveys administered to 265 students with monitoring of digital media, including social networks, to identify the consumption of political information and the verification strategies used. The results reveal that the majority of students are informed through of social networks, mainly Facebook and TikTok, and that there is a medium-high impact of fake news on their political perception. Likewise, it was identified that the most consumed topics are electoral and government issues, and that the verification strategies used by students are limited, with low use of fact-checking tools. The research concludes that, although students recognize some characteristics of fake news, the lack of adequate verification processes makes them vulnerable to misinformation. It is recommended to implement media literacy programs, promote critical thinking and strengthen training in the analysis of false news. information sources to reduce the impact of misinformation in the university community.
Las noticias falsas o fake news representan un problema significativo en la sociedad actual, especialmente en el ámbito político, donde su difusión puede influir en la percepción y toma de decisiones de los ciudadanos esta investigación analiza el impacto de las noticias falsas sobre política nacional en la percepción de los estudiantes de los primeros semestres de la Facultad de Ciencias Sociales de la Universidad Técnica de Machala. El estudio empleó un enfoque mixto, combinando encuestas aplicadas a 265 estudiantes con un monitoreo de medios digitales, incluyendo redes sociales, para identificar el consumo de información política y las estrategias de verificación utilizadas los resultados revelan que la mayoría de los estudiantes se informan a través de redes sociales, principalmente Facebook y TikTok, y que existe un impacto medio-alto de las noticias falsas en su percepción política asimismo, se identificó que los temas más consumidos son asuntos electorales y de gobierno, y que las estrategias de verificación utilizadas por los estudiantes son limitadas, con un bajo uso de herramientas de fact-checking. La investigación concluye que, si bien los estudiantes reconocen algunas características de las noticias falsas, la falta de procesos adecuados de verificación los hace vulnerables a la desinformación se recomienda implementar programas de alfabetización mediática, promover el pensamiento crítico y fortalecer la formación en el análisis de fuentes informativas para reducir el impacto de la desinformación en la comunidad universitaria.
Keywords: FAKE NEWS; DISINFORMATION; FACT-CHECKING; SOCIAL NETWORKS; ELECTORAL INFLUENCES; DECISION MAKING